Comparison of Alpha-Fetoprotein Level in Varying Severity Degree of Hepatocellular Carcinoma Assesed with the Barcelona Clinic of Liver Cancer During 2015-2016 in Haji Adam Malik General Hospital Medan - Gontar Alamsyah Siregar; Sri Ningsih Lubis (The Indonesian Society for Digestive Endoscopy, 2017)
Background: Hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related deaths worldwide. Presently, the reference staging system to evaluate the prognosis of HCC is The Barcelona Clinic Liver Cancer (BCLC) system. The aim of the study was to identify the comparison of alpha-fetoprotein (AFP) level in varying severity degree of HCC patient assessed with BCLC.Method: This retrospective observational study used patients’ medical record hospitalized for HCC between January 1st 2015 until December 31st 2016 in Adam Malik Hospital. From 166 HCC patients with AFP, liver function test (LFT), home sleep test (HST), ultrasonography (USG), and computerized tomography (CT) scan liver 3 phase were included in this study. The comparison of AFP in severity of HCC based on BCLC system was analyzed.Results: About 77.7% HCC patients were male. The mean age was 52 ± 13.63 years. The most cause of HCC was hepatitis B infection. Median AFP was 574.97 ng/mL. According to the BCLC staging system, 12 patients were classified as stage A (7.2%), 54 patients stage B (32.5%), 76 patients stage C (45.8%) and 24 patients stage D (14.5%). There’s significance difference value of AFP in varying stage of BCLC for HCC, which the highest value in BCLC stage D, followed by C, B and A (p = 0,001)Conclusion: There’s significance difference value of AFP in varying stage of BCLC for HCC patients.